On Appearance/ Apparition and Disappearance in the poem "Angel de rigor", By Enrique Lihn (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This paper deals with the symbolic and semiotic discourse of the poem "Angel de Rigor" by Enrique Lihn. This poem is characterized by its "situated poetry", which accepts the bitter parody of the common places derived from western lyrical tradition. The ironic attitude of the subject of its enunciation comes out decisive to set up in this receptive discourse. This type of discourse reaches a more embracing dimension of Lihn's work as it relates to certain intertextualities. Thus, the significant chain of "Angel de rigor" clearly matches with the "sense" and meaning that flow from the global lyrical production of Chilean poet, Enrique Lihn. Among other factors, these features set forth a given specificity in Lihn's work, that is, the artistic oddity and the possibility to transport Lihn's poetry to the present.
Keywords: Lihn; Chilean poetry; intertextualities; situated poetry